Violent attacks on Middle Easterners in the United States during the month following the September 11, 2001 terrorist attacks. Issue 2 (1st June 2003) - Swahn, M H; Mahendra, R R; Paulozzi, L J; Winston, R L; Shelley, G A; Taliano, J; Frazier, L; Saul, J R
Abstract : Objectives: To document and describe hate related violent attacks on Middle Easterners or those perceived to be Middle Easterners during the month following the September 11, 2001 terrorist attacks in New York City and Washington, DC. Methods: The LexisNexis database of newspaper reports were used to identify incidents of hate related violent acts against Middle Easterners or those perceived to be Middle Easterners in the US between September 1 and October 11, 2001. A total of 100 incidents of hate related violence were identified in the 2659 news articles that were reviewed. Results: Of the 100 incidents of violent victimization that took place during the period September 1 to October 11, only one incident occurred before September 11. The 99 incidents that occurred after September 11 involved at least 128 victims and 171 perpetrators. Most violent victimizations occurred within 10 days of the attacks, involved male perpetrators and male victims, and occurred in convenience stores, on the streets, at gas stations, at schools/colleges, and at places of worship. Discussion: Most violent victimizations occurred in the 10 days immediately following the terrorist attacks indicating that interventions that promote tolerance and understanding of diversity need to be implemented quickly in order to be effective. In addition, patrolling by police and Neighborhood Watch programs around convenience stores and gas stations may also be effective strategies for reducing hate related violent crimes.